ANALISIS KINERJA PHOTOVOLTAIK PADA STAND ALONE - Herman HR (Jurnal Teknik Mesin Sinergi, 2017)
Solar Power Generation (SPG), or often called solar photovoltaic system, is one application of the use of solar energy as a source of electrical energy. This PLTS utilizes solar cells (photovoltaic) to generate electrical energy. The aimed of this research were to know the performance of PLTS installed power 150 Wp stand alone and know how much power capacity can be supplied by PLTS. Solar Power Generation (Photovoltaics) most influenced by the intensity of sunlight depending on each region. Module with a capacity of 150 Wp has been able to produce a mean power of 133.7 Watt / day. The expected output in this research was to create a good system and can contribute to student labs in laboratories and as an alternative source of energy in the Department of Mechanical Engineering and Maintenance, and beneficial for the development of electric power generation system in district of Fak-fak. This research was also expected to produce Scientific Publications in local journals.